2012
DOI: 10.1159/000346205
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exercise Training on Circulating Retinol-Binding Protein 4 and Cardiovascular Disease Risk Factors in Obese Men

Abstract: Introduction: The purpose of this study was to investigate the effects of 12-week exercise training on circulating retinol-binding protein 4 (RBP4) concentration and cardiovascular disease (CVD) risk factors in obese men. Methods: 29 obese men (age 48 ± 2 years; BMI 29.6 ± 0.7 kg/m2) participated in a 12-week exercise program (50–70% maximal heart rates; 3 times/week) without calorie restriction. Anthropometric parameters, CVD risk factors (total cholesterol, high-density lipoprotein cholesterol (HD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 77 publications
0
26
0
Order By: Relevance
“…The second phase of training failed to induce further significant decline in leptin levels. Ten studies provided additional pre- and post-training adiponectin levels [ 32 , 33 , 36 , 38 , 40 , 41 , 44 , 45 , 48 , 49 ], 13 reported indicators of carbohydrate metabolism ( Table 2 ) [ 36 45 , 48 50 ], 11 reported training-induced BMI changes [ 35 , 36 , 39 45 , 49 , 50 ], a partially different subset of 11 studies described training-induced changes in fat mass [ 34 , 39 45 , 48 50 ]. From the 18 studies that investigated the effects of training on leptin levels [ 32 45 , 47 50 ] only 3 of them failed to detect significant effect [ 43 , 45 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The second phase of training failed to induce further significant decline in leptin levels. Ten studies provided additional pre- and post-training adiponectin levels [ 32 , 33 , 36 , 38 , 40 , 41 , 44 , 45 , 48 , 49 ], 13 reported indicators of carbohydrate metabolism ( Table 2 ) [ 36 45 , 48 50 ], 11 reported training-induced BMI changes [ 35 , 36 , 39 45 , 49 , 50 ], a partially different subset of 11 studies described training-induced changes in fat mass [ 34 , 39 45 , 48 50 ]. From the 18 studies that investigated the effects of training on leptin levels [ 32 45 , 47 50 ] only 3 of them failed to detect significant effect [ 43 , 45 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Regarding gender, 6 studies reported data of men [ 36 , 40 , 41 , 43 , 44 , 46 ], 5 reported data of women [ 32 , 35 , 37 , 38 , 50 ], the remaining 8 merged data of men and women [ 33 , 34 , 39 , 42 , 45 , 47 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…We did not measure inflammatory markers and cardiovascular risk factors. Previous studies demonstrated that RBP4 concentrations were associated with inflammatory markers such as C-reactive protein [17] and cardiovascular risk factors such as triglyceride [9] , total cholesterol [6] and low density lipoprotein (LDL) cholesterol [6] . If we could measure these markers, we could carefully explain the changes of RBP4 concentrations in response to 8 weeks exercise training in female athletes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have provided evidence that mindfulness-based and cognitive-behavioural interventions can decrease both peripheral as well as stimulated pro-inflammatory cytokines, including IL-6 and TNF-α, along with decrease in stress, anxiety and depression scores (Zautra et al 2008;Lengacher et al 2012;Rosenkranz et al 2013). Similarly, evidence suggests that unhealthy dietary patterns contribute to pro-inflammatory as well as psychopathological phenotypes (Lucas et al 2014;André et al 2014), whilst exercise, calorie restriction or supplementation with omega-3 polyunsaturated fatty acids can decrease inflammation and improve mental well-being (Kiecolt-Glaser et al 2011;Numao et al 2012;MacDonald et al 2014;Cairns et al 2014). This literature review underlines the importance of appreciating the wider host of factors that can interact with inflammatory function when considering the possible therapeutic effects of psychotropic drugs via inflammatory modulation (Fig.…”
Section: Future Research Directions and Remaining Issuesmentioning
confidence: 99%